1996
DOI: 10.3758/bf03213295
|View full text |Cite
|
Sign up to set email alerts
|

Group aggregates and individual reliability: The case of verbal short-term memory

Abstract: Two experiments examined the generalizability of the effects of word length and phonological similarity with visual and auditory presentation in immediate verbal serial ordered recall. In Experiment 1, data were collected from 251 adult volunteers drawn from a broad cross-section of the normal population. Word length and phonological similarity in both presentation modes significantly influenced the group means. However, 43% of the subjects failed to show at least one of the effects, and the likelihood that ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
177
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(197 citation statements)
references
References 45 publications
(56 reference statements)
17
177
1
1
Order By: Relevance
“…Indeed phonological factors such as word length and phonological similarity did not consistently influence STM performance in our 4 WS subjects. However, it has to be noted that these effects are not always consistent in normal subjects either; for example, Logie et al (1996) showed that these effects can also be absent in normal subjects. More importantly, the phonotactic frequency effect which was consistently observed in our CA-and VA-matched control subjects, but was strongly reduced or even inversed in the four WS children, further suggests that phonological language knowledge influences less consistently their performance in phonological STM tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed phonological factors such as word length and phonological similarity did not consistently influence STM performance in our 4 WS subjects. However, it has to be noted that these effects are not always consistent in normal subjects either; for example, Logie et al (1996) showed that these effects can also be absent in normal subjects. More importantly, the phonotactic frequency effect which was consistently observed in our CA-and VA-matched control subjects, but was strongly reduced or even inversed in the four WS children, further suggests that phonological language knowledge influences less consistently their performance in phonological STM tasks.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, when a subsample of 40 individuals, 20 of whom failed to show one of the expected effects in the four conditions of the original experiment, was retested at a later point, very low test-retest reliability of the size of the phonological similarity or word length effects was observed. Nevertheless, at the sample level Logie et al (1996) found that the absolute size of an individual's phonological similarity or word length effect was related to their level of overall recall, and was related to whether or not participants reported using subvocal rehearsal as a memory strategy. Beaman et al (2008) replicated the finding that the magnitude of the phonological similarity and word length effects shown by adult undergraduates was proportional to individuals' level of recall.…”
mentioning
confidence: 97%
“…These authors examined the size of both the phonological similarity and the word length effects shown by a large sample (n = 251) of adult participants drawn from the general population. Logie et al (1996) found that a number of their sample failed to show reliable phonological similarity or word length effects, under conditions of either auditory or visual presentation. The extent to which these effects were absent was not particularly consistent across, and even within, participants, with some individuals showing an absent effect on one measure or in one modality in combination with a reliable effect on the other measure or in the other modality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data on children's speech rate-span correlations are more equivocal than is often thought (Jarrold & Hall, 2013), and such correlations may be particularly 'noisy' in young children. In addition, a reduction in the size of the word length and phonological similarity effects to non-significant levels in young children may simply reflect the fact that these effects scale proportionally (Beaman, Neath, & Surprenant, 2008;Logie, Della Sala, Laiacona, Chambers, & Wynn, 1996), and are therefore hard to detect in absolute terms among individuals whose overall recall levels are low (Jarrold, Danielsson, & Wang, 2015;Wang, Logie, & Jarrold, in press). Indeed, we have shown that children younger or older than 7 show comparable effects of phonological similarity for visually presented materials when these effects are analysed in proportional terms (Jarrold & Citroën, 2013).…”
Section: Working Out How 15mentioning
confidence: 99%